The Early Years : Assessing and Promoting Resilience in Vulnerable Children 1 - Daniel, Brigid (Jessica Kingsley Publishers, 2002)
This clear and practical workbook shows the importance of encouraging resilience in pre-school children who live in challenging circumstances. Focusing on assessment of need, Brigid Daniel and Sally Wassell show how to evaluate resilience using checklists and background information. They explain that children in their early years gain resilience from a range of experiences, including attachment relationships, opportunities to develop self-esteem and learning to understand others and behaving in a positive way towards them. With this in mind, they set out ways of encouraging pro-social behaviou.